Gut Microbiota in HIV Infection: Implication for Disease Progression and Management - Nwosu, Felix Chinweije (Hindawi Publishing Corporation, 2014)
Survival rates among HIV patients have significantly improved since the introduction of antiretroviral therapy (ART) in HIV management. However, persistent disease progression and clinical complications in virally suppressed individuals point to additional contributing factors other than HIV replication; microbial translocation is one such factor. The role of underlying commensal microbes and microbial products that traverse the intestinal lumen into systemic circulation in the absence of overt bacteraemia is under current investigation. This review focuses on current knowledge of the complex microbial communities and microbial markers involved in the disruption of mucosal immune T-cells in the promotion of inflammatory processes in HIV infections. Unanswered questions and aims for future studies are addressed. We provide perspective for discussing potential future therapeutic strategies focused on modulating the gut microbiota to abate HIV disease progression.